2014
DOI: 10.1371/journal.pone.0111390
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surface Markers between Human and Rabbit Mesenchymal Stem Cells

Abstract: This study investigated whether there are marked differences in surface markers between rabbit and human mesenchymal stem cells (MSCs). Murine and rabbit MSCs have been reported to be CD90-negative. Rat MSCs have been reported to be CD71-negative. Our previous study also shows that rabbit MSCs are CD29-negative. However, human MSCs are generally considered to be CD29-, CD71-, and CD90-positive. Therefore, the surface markers of human MSCs might differ from those of other species. Rabbit bone marrow MSCs were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 16 publications
7
43
0
Order By: Relevance
“…For this reason, investigators tend to use a set of different markers typical of a particular MSC population in the identification of these. Therefore, in addition to the detection of cell surface markers, we chose to detect mesechymal stem cell specific intracellular markers previously detected in rabbit and human BM‐MSCs . The expression of vimentin, α‐SMA, and desmin we detected was very similar to that described in a study conducted on rabbit BM‐MSCs (97.42% ± 0.71%; 93.69% ± 3.23%; 59.65% ± 8.13% vs. 95.68% ± 3.58%; 95.10% ± 2.00%; 77.91% ± 1.78%).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…For this reason, investigators tend to use a set of different markers typical of a particular MSC population in the identification of these. Therefore, in addition to the detection of cell surface markers, we chose to detect mesechymal stem cell specific intracellular markers previously detected in rabbit and human BM‐MSCs . The expression of vimentin, α‐SMA, and desmin we detected was very similar to that described in a study conducted on rabbit BM‐MSCs (97.42% ± 0.71%; 93.69% ± 3.23%; 59.65% ± 8.13% vs. 95.68% ± 3.58%; 95.10% ± 2.00%; 77.91% ± 1.78%).…”
Section: Discussionsupporting
confidence: 54%
“…An extensive study of human and rabbit MSC surface markers using RT‐PCR and flow cytometry should be conducted in the future . To the best of our knowledge, we are the first to report a discrepancy between mRNA levels and corresponding surface marker protein expression (as detected by species‐specific antibodies) in rAF‐MSCs.…”
Section: Discussionmentioning
confidence: 93%
“…For the in vitro experiments, immunofluorescence staining was performed for CD31, an endothelial cell marker, and α-smooth muscle actin (αSMA), expressed by hMSCs [46]. Following fixation in 10% buffered formalin (Fisher Scientific, Pittsburgh, PA), samples were washed with PBS, permeabilized with 0.5% Triton-X in PBS (PBST), and blocked with 6% normal goat serum (MP Biomedicals, Solon, OH) for one hour.…”
Section: Methodsmentioning
confidence: 99%
“…Lee et al [27] have demonstrated that CD14, CD31, CD34, CD45, CD49d, CD49f, CD51, CD54, CD71, CD106, CD133, major histocompatibility complex (MHC II), cytokeratin, and desmin were absent from human MSCs, whereas CD13, CD29, CD44, CD59, CD73, CD90, CD105, CD166, MHC I,a-SMA, and vimentin were present on human MSCs. For human bone marrow stromal cells, common targets of negative antigene expression include CD2, CD3, CD11b/Integrin alpha M, CD14, CD15/Lewis X, CD16/F c gamma RIII, CD19, CD38, CD56/NCAM-1, CD66b/CEACAM-8, CD123/IL-3 R alpha, and CD235a/Glycophorin.…”
Section: According To the Mesenchymal And Tissue Stem Cell Committee mentioning
confidence: 99%